SEX REASSIGNMENT SURGERY (TRANSGENDER) IN INDONESIA EXAMINED FROM THE PERSPECTIVE OF CRIMINAL LAW - Evelina, Renita; Fitriasih, Surastini (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
The rising trend of LGBT (Lesbian, Gay, Bisexual, and transgender) cases in the world, include Indonesia is triggering worries about increasing demand of sex reassignment surgery (transgender). On the other hand, the issue about sex reassignment surgery is a very controversial issue, especially Indonesia. By looking to the existing data and facts, Indonesia can not deny that there are LGBT people in Indonesia. Criminal law should be responsive to the facts in society, including the controversial issie like sex reassignment surgery. This article discusses about sex reasignment surgery viewed from Indonesian criminal law perspective by using doctrinal research method. This article was written by reviewing regulations, especially Law of the Republic of Indonesia Number 17 of 2023 concerning Health and Law of the Republic of Indonesia Number 1 of 2023 concerning the Criminal Code as the main reference. This study aims to look at criminal law regulations regarding sex reassignment surgery in Indonesia as well as to review the function of criminal law as a tool for balancing between public interests and individual interests. The findings of this study show that the criminal policy applied to regulate sex reassignment surgery is in the form of criminal sanction for every doctor who performs sex reassignment surgery without therapeutic purposes. This study also shows how important it is to ensure the conditions under which the sex reassignment surgery in Indonesia is performed in order to protect the doctors carrying out the work.